The oral-gut microbiota axis: a link in cardiometabolic diseases - Qian Xu; Wenting Wang; Yiwen Li; Jing Cui; Mengmeng Zhu; Yanfei Liu; Yue Liu (npj Biofilms and Microbiomes)
Abstract The oral-gut microbiota axis plays a crucial role in cardiometabolic health. This review explores the interactions between these microbiomes through enteric, hematogenous, and immune pathways, resulting in disruptions in microbial balance and metabolic processes. These disruptions contribute to systemic inflammation, metabolic disorders, and endothelial dysfunction, which are closely associated with cardiometabolic diseases. Understanding these interactions provides insights for innovative therapeutic strategies to prevent and manage cardiometabolic diseases.